Tinjauan Potensi Pemanfaatan Botol Bekas Berbahan Polyethylene Terephthalate (PET) di Indonesia - Gema Fitriyano; Dicka Ar Rahim (Eksergi, 2019)
The use of bottles made from Polyethylene Terephthalate (PET) has been increasing along with the development of ready-to-drink products. This type of packaging is very popular with the beverage industry because it is easily formed, strong, transparent, hygienic and economical. The increase in the use of PET bottles has an impact on the amount of waste that also increases so that it can become an environmental problem if it is not handled properly. The waste is still untapped in Indonesia, its utilization has only reached the stage of producing PET chopped which are then exported to countries that have beverage bottle recycling industries. This study aims to review the handling of used bottle waste, processing methods, shortcomings and advantages of products where this review is based on industry data and scientific articles. The consumption of beverages in PET bottle packaging which is increasing every year is a very promising potential for the development of research and the construction of industries related to processing used PET bottles in Indonesia